Effects of selenium-mediated RUNX2 overexpression and its transcriptome alterations on Chondrocyte injury in Kashin Beck disease - Zhang, Di; Li, Qiang; Yang, Xiaoli; Xiong, Yongmin; Sun, Shiquan (Frontiers in Cell and Developmental Biology, 2025)
ObjectiveKashin-Beck disease (KBD) is a nutrition-related osteoarthropathy characterized by excessive apoptosis and matrix destruction. Micronutrient selenium (Se) deficiency is recognized as a major environmental risk factor. This study aimed to investigate the role of RUNX2 in cartilage injury associated with KBD.MethodsRUNX2 expression in articular cartilage from KBD patients was assessed by immunohistochemistry. RUNX2 mRNA expression and promoter methylation were analyzed using qRT-PCR and qMSP. A chondrocyte injury model was established under Se-deficient conditions, while a RUNX2 overexpression model was generated by lentiviral transfection and further analyzed by RNA sequencing.ResultsThe proportion of RUNX2-positive cells in KBD cartilage was significantly higher than in controls. RUNX2 mRNA levels were elevated, whereas methylation levels were reduced in KBD samples. Inhibition of DNA methylation confirmed that decreased methylation of RUNX2 promoted its transcription. In Se-deficient chondrocytes, decreased RUNX2 methylation, increased RUNX2 expression, and higher rates of apoptosis and necrosis were observed, all of which were reversed by Se supplementation. Moreover, RUNX2 overexpression further increased chondrocyte apoptosis and necrosis. Transcriptomic analysis revealed 263 upregulated and 216 downregulated genes, predominantly enriched in the TNF and MAPK signaling pathways.ConclusionMicronutrient Se deficiency may contribute to the pathogenesis of KBD by modulating RUNX2 expression and inducing excessive chondrocyte apoptosis, while Se supplementation exerts a protective effect. RUNX2 plays a critical role in KBD progression and may represent a potential therapeutic target.